THE ROLE of OXIDATIVE STRESS and LIPID PEROXIDATION IN VENTRICULAR REMODELING INDUCED BY TOBACCO SMOKE EXPOSURE AFTER MYOCARDIAL INFARCTION - Duarte, Daniella R. [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Gaiolla, Paula Schmidt Azevedo [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Novelli, Ethel L. [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP] (Universidade de São Paulo (USP), Hospital das Clínicas, 2009)
OBJECTIVE: To evaluate the roles of oxidative stress and lipid peroxidation in the ventricular remodeling that is induced by tobacco smoke exposure after myocardial infarction.METHODS: After induced myocardial infarction, rats were allocated into two groups: C (control, n=25) and ETS (exposed to tobacco smoke, n=24). After 6 months, survivors were submitted to echocardiogram and biochemical analyses.RESULTS: Rats in the ETS group showed higher diastolic (C = 1.52 +/- 0.4 mm(2), ETS = 1.95 +/- 0.4 mm(2); p=0.032) and systolic (C = 1.03 +/- 0.3, ETS = 1.36 +/- 0.4 mm(2)/g; p=0.049) ventricular areas, adjusted for body weight. The fractional area change was smaller in the ETS group (C = 30.3 +/- 10.1 %, ETS = 19.2 +/- 11.1 %; p=0.024) and E/A ratios were higher in ETS animals (C = 2.3 +/- 2.2, ETS = 5.1 +/- 2.5; p=0.037). ETS was also associated with a higher water percentage in the lung (C = 4.8 (4.3-4.8), ETS = 5.5 (5.3-5.6); p=0.013) as well as higher cardiac levels of reduced glutathione (C = 20.7 +/- 7.6 nmol/mg of protein, ETS = 40.7 +/- 12.7 nmol/mg of protein; p=0.037) and oxidized glutathione (C = 0.3 +/- 0.1 nmol/g of protein, ETS = 0.9 +/- 0.3 nmol/g of protein; p=0.008). No differences were observed in lipid hydroperoxide levels (C = 0.4 +/- 0.2 nmol/mg of tissue, ETS = 0.1 +/- 0.1 nmol/mg of tissue; p=0.08).CONCLUSION: In animals exposed to tobacco smoke, oxidative stress is associated with the intensification of ventricular re-remodeling after myocardial infarction.
Keywords: Ventricular function; Coronary occlusion; Ventricular dilatation; Hypertrophy; Heart failure